The living conditions of childworkers' families in a sugarcane farm community - Gamboa, Willie Leonida; Servidad, Felix de la Cruz, Jr. (2002.)
The study aims to know the socio-demographic characteristics and living conditions of child worker's families in a sugarcane farm community. Likewise, it deals with the families' perception on their children's early participation to work but there will be no depth treatment. The study was conducted in Hacienda Bagacay, Barangay Bagtic, Silay City, Negros Occidental. From the hacienda administration's census, 30 respondents were obtained using the fishbowl method of simple random sampling. A combination of open-ended questions comprised the interview schedule used for gathering data. Like any families in the sugarcane farm, child worker's families are poor and generally large with many young household members. However, most of them do not consider their living conditions as poor. As a whole, child workers has been part of the lives of this poverty-stricken community.
Research Project (Bachelor of Arts Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Children -- Employment